Anxiety and Posttraumatic Stress Symptom Pathways to Substance Use Problems among Community Women Experiencing Intimate Partner Violence - Jaquier, Véronique (Anxiety Stress Coping, 2014)
This study examines effects of psychological, physical, and sexual intimate partner violence (IPV) to alcohol and drug problems through anxiety and posttraumatic stress symptom severity among 143 community women currently experiencing IPV. Anxiety and posttraumatic stress symptom severity had unique effects on alcohol and drug problems. Higher anxiety symptom severity and higher physical IPV severity were associated with greater alcohol and drug problems. Higher posttraumatic stress symptom severity was associated with greater alcohol and drug problems. Mediation analyses indicated (a) significant indirect pathways of IPV types to alcohol problems through posttraumatic stress symptom severity controlling for anxiety symptom severity, and (b) significant indirect pathways of IPV types to drug problems through anxiety symptom severity controlling for posttraumatic stress symptom severity. In examining the indirect pathways of psychological, physical, and sexual IPV to substance use problems this study highlights that anxiety and posttraumatic stress symptom severity have unique effects on alcohol and drug problems among women experiencing IPV.